The Effect of Customer Delight, Brand Image, and Product Innovation on The Purchase Decision of The Erigo Brand in The City of Surabaya - Siti Mujanah; Rafif Satriatama (Journal of Applied Management and Business, 2022)
This study aims to determine the effect of customer satisfaction, Brand image, and Product innovation on consumer Purchasing of Erigo brand products in Surabaya. This type of research is quantitative research. The population is all customers of the Erigo brand in Surabaya. The number of samples taken is 100 respondents who are taken incidentally. The sampling technique used is the prior probability sampling technique; this technique is randomization or coincidence. The data collection method used is a survey with a questionnaire instrument that is using a questionnaire. The result of this study shows that customer delight; in the brand image has a significant effect on purchasing decisions but not on product innovation which is not significant for purchasing decisions for the Erigo brand in the city of Surabaya. Meanwhile, simultaneously, Customer delight, brand image, and product innovation influence purchasing decisions for the Erigo brand in Surabaya.